Implementasi Penerapan Psak 409 Terhadap Akuntansi Zakat, Infak, Dan Sedekah Pada Baznas Kota Palembang - Haliza, Nadya Wanda; Anggraini, Niken; Hanifah, Ulfah Aulia; Azwari, Peny Cahaya (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
. This research examines the implementation of PSAK 409 in the management of zakat, infak, and sedekah at BAZNAS Kota Palembang. The study utilizes a qualitative approach through literature review to analyze various aspects of compliance with PSAK 409, focusing on challenges and supporting factors. Findings indicate significant progress in implementing standards, yet reveal persistent challenges in recognition, measurement, and financial report presentation. Key supporting factors include robust regulations, structured accounting guidelines, and effective internal audits. However, limitations such as insufficient understanding of accounting standards and inadequate technological infrastructure hinder optimal implementation. This research recommends a comparative study involving various zakat management institutions across different regions for broader insights and best practices